Phytochemical Investigation of Aerial Parts of Iraqi Cardaria draba - Abd, Alaa M.; J. Kadhim, Enas (Iraqi Journal of Pharmaceutical Sciences, 2020)
The aim of this study was to study chemical constituents of aerial parts of Cardaria draba since no phytochemical investigation had been studied before in Iraq. Aerial parts of Cardaria draba were defatted by maceration in hexane for 72 h. The defatted plant materials were extracted using Soxhlet apparatus, the aqueous Methanol 90% as a solvent extraction for 18 h, and fractionated with petroleum ether- chloroform (CHCl3)- ethylacetate- and n-butanol respectivly. The ethyl acetate, n-butanol, and n-butanol after hydrolysis fractions were investigated by high performance liquid chromatography (HPLC) and thin-layer chromatography (TLC) for its phenolic acid and flavonoid contents. Flavonoids and phenolic acid derivative were isolated from the ethylacetate of leaf fraction and n-butanol after hydrolysis fraction of the aerial parts and identified by TLC, FTIR and HPLC. A various chromatographic and spectroscopic results shown the presence of luteolin, chlorogenic acid, caffeic acid, and resorcinol in aerial parts of C. draba.